Free student hours and their role in reducing the spread of drug use in the university environment (obstacles and solutions) - جواد, م.د حسنين عبد الرزاق; Mansour, Dr. Ahmed Kadhim (Sulaimani Journal for Humanities, 2026)
Having worked in the Student Activities Department for several years, the researchers gained firsthand knowledge of all aspects of student life at the University of Babylon. They recognized the importance of extracurricular activities (sports, arts, and scouting) in alleviating academic pressures and depression, thus mitigating the risk of students resorting to tranquilizers and ultimately drugs (a modern-day scourge). Therefore, they decided to conduct an analytical study of the University of Babylon's student body as a representative model for other Iraqi universities. The aim was to demonstrate the significance of extracurricular activities in curbing drug use and to identify obstacles and solutions for protecting students from succumbing to this dangerous phenomenon. To this end, the researchers developed questionnaires addressing various obstacles (administrative and organizational, recreational and leisure facilities such as sports halls and fields, art studios and theaters, scouting environment, and other equipment, as well as personal obstacles), in addition to questionnaires specifically addressing drug use. These questionnaires consisted of several items to be answered. The research objective was to identify the impact of University of Babylon students' participation in extracurricular activities (sports, arts, and scouting). To identify the qualitative obstacles to free student hours (sports, arts, scouting) for students at the University of Babylon. To identify differences in drug use among University of Babylon students based on the variables of academic specialization and gender. As for the research methodology: the researchers used the descriptive method with a random sampling approach, employing survey and correlational methods. As for the research population and samples: this was represented by defining the research population as students of the University of Babylon, represented by (10) colleges out of (20) colleges, from various academic, scientific, and humanities specializations, and from different stages (first, second, third, and fourth), totaling (948) students, registered in the college records for the academic year 2024-2025, including (820) male and female students, representing (86.5%), and they were selected using the random method. The research sample consisted of students from the University of Babylon, specializing in scientific and humanities disciplines (Civil Engineering, Materials Engineering, Information Technology, Physics, Chemistry, Basic Education, Humanities, Arts, Law, Fine Arts), from five scientific colleges and five humanities colleges, totaling (99) students, representing 60 male students and 39 female students, representing 10.4% of the total population, representing the pilot study. The main experiment involved applying the questionnaire to a group of University of Babylon students (male and female) from various scientific and humanities disciplines for the academic year 2024-2025. The researchers ensured uniformity in the method of dealing with the questionnaire within the second axis in terms of general instructions, the method of filling out the forms, and writing the basic data. After completing the application of the questionnaire, the data were extracted to be statistically processed using appropriate scientific statistical methods. The most important conclusions were: Students' opinions, which were relatively high, varied regarding their conviction in the importance of facilities and equipment (sports fields, sports halls, exhibitions, scouting camps, etc.) in spending leisure and recreational time at the university, indicating a positive relationship between their availability and students' reluctance to actively participate in them. Significant differences were found between students' opinions on most statements in the three sections of the obstacles and the second questionnaire on drugs, reflecting the different priorities given to participation in free student hours by male and female students. Students' opinions reflected the weakness of participation in and contribution of student activities to achieving university goals
Keywords: Free student hours; university life; drug use; obstacles and solutions